Adopting react Personal Health Record (PHR) system in Yemen healthcare institutions - Alrobieh, Ziad Saif (2021)
Health care is a critical sector of society that requires quality improvement of healthcare services, information technology IT systems have a great impact on improving the quality of these services, unfortunately, The effect of information culture on the implementation of information systems by healthcare providers in the developed countries is little known, considering the importance of information culture. Despite that many Yemeni healthcare facilities have been already using information systems to digitize the management of healthcare providing procedures, The patients’ health information including disease history and prescriptions is not fully recorded and additionally, there is no implementation of Personal Health Record PHR systems where patients can access, and control their health records from another place where their records are stored locally in the healthcare providers’ databases. The existing electronic health record systems are limited and do not exploit the available technology solutions and services. To explore the advantages of using PHR systems, multiple kinds of research are being studied and the proof of use has been cleared by these researchers’ conclusions, also a survey was made, to ensure people intention to using PHR systems, and to observe their opinion on what they need to be provided by the system and what interests them. Designing the web-based system was done after going through the available platforms to choose the most correct and suitable solutions to assure that the system meets the requirements needed. Adopting innovative and modern technological solutions such as PHR web applications is a fine way to improve patient safety and quality of care, increase efficiency, Decision supporting, and Increase patient and health workers’ satisfaction. The proposed solution ensured the patients’ satisfaction and safety by giving them access to their health records whenever and wherever they are through their device’s browser and helped the doctors to make the right decisions and speed up the healthcare providing process which reduced the damage caused by the current systems, saving human lives and preventing serious health issues.